Autophagy-mediated occludin degradation contributes to blood-brain barrier disruption during ischemia in bEnd.3 brain endothelial cells and rat ischemic stroke models - Kim, Kyeong A.; Kim, Donghyun; Kim, Jeong Hyeon; Shin, Young Jun; Kim, Eun Sun; Akram, Muhammad; Kim, Eun Hye; Majid, Arshad; Baek, Seung Hoon; Bae, Ok Nam (Fluids and Barriers of the CNS, 2020)
Background: The blood-brain barrier (BBB) maintains homeostasis of the brain environment by tightly regulating the entry of substances from systemic circulation. A breach in the BBB results in increased permeability to potentially toxic substances and is an important contributor to amplification of ischemic brain damage. The precise molecular pathways that result in impairment of BBB integrity remain to be elucidated. Autophagy is a degradation pathway that clears damaged or unnecessary proteins from cells. However, excessive autophagy can lead to cellular dysfunction and death under pathological conditions. Methods: In this study, we investigated whether autophagy is involved in BBB disruption in ischemia, using in vitro cells and in vivo rat models. We used brain endothelial bEnd.3 cells and oxygen glucose deprivation (OGD) to simulate ischemia in culture, along with a rat ischemic stroke model to evaluate the role of autophagy in BBB disruption during cerebral ischemia. Results: OGD 18 h induced cellular dysfunction, and increased permeability with degradation of occludin and activation of autophagy pathways in brain endothelial cells. Immunostaining revealed that occludin degradation is co-localized with ischemic autophagosomes. OGD-induced occludin degradation and permeability changes were significantly decreased by inhibition of autophagy using 3-methyladenine (3-MA). Enhanced autophagic activity and loss of occludin were also observed in brain capillaries isolated from rats with middle cerebral artery occlusion (MCAO). Intravenous administration of 3-MA inhibited these molecular changes in brain capillaries, and recovered the increased permeability as determined using Evans blue. Conclusions: Our findings provide evidence that autophagy plays an important role in ischemia-induced occludin degradation and loss of BBB integrity.
Keywords: Animals; Autophagy; Blood-Brain Barrier; Brain Ischemia; Cells, Cultured; Disease Models, Animal; Endothelial Cells; Infarction, Middle Cerebral Artery; Occludin; Rats; Stroke; Autophagy; Blood-brain barrier (BBB); Ischemic stroke; Middle cerebral artery occlusion (MCAO); Occludin; Oxygen-glucose deprivation (OGD)